2023
DOI: 10.3390/ma16206800
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Improve the Reliability of High-Strength Concrete Strength Evaluation Using an Ultrasonic Velocity Method

Wonchang Kim,
Taegyu Lee

Abstract: The ultrasonic pulse velocity (UPV) technique, which is an efficient technique for concrete quality evaluation, can be affected by several factors. Many studies have proposed compressive-strength prediction models based on UPV in concrete; however, few studies have investigated the factors resulting in statistically different UPV results for different models. This study examined the difference between compressive strengths of various concrete specimens calculated by age-dependent and temperature-dependent UPV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In the case of post-high-temperature exposure, there was a significant difference in the compressive strength according to the W/C ratio; however, UPV followed the opposite trend. This implied that concrete with a low W/C ratio under a constant UPV exhibits a high compressive strength, which agrees well with the results from previous studies [ 21 ]. Therefore, the W/C ratio is highlighted as an important factor in the development of a concrete strength prediction model using UPV after high-temperature exposure [ 44 , 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the case of post-high-temperature exposure, there was a significant difference in the compressive strength according to the W/C ratio; however, UPV followed the opposite trend. This implied that concrete with a low W/C ratio under a constant UPV exhibits a high compressive strength, which agrees well with the results from previous studies [ 21 ]. Therefore, the W/C ratio is highlighted as an important factor in the development of a concrete strength prediction model using UPV after high-temperature exposure [ 44 , 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 92%
“…Previous studies tested the statistical significance of the strength and UPV of heated and unheated concrete, and the results of the regression analysis were evaluated [ 21 ]. Concrete with a high-temperature history in the same UPV range showed a relatively high prediction rate in terms of compressive strength, and it was reported that crack formation owing to differences in the thermal expansion properties of mixed materials and voids owing to chemical decomposition contributed to the very low UPV [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the non-destructive techniques employed for estimating compressive strength, the use of ultrasonic pulse velocity (UPV), which employs ultrasonic waves, has gained prominence. Consequently, numerous researchers are employing UPV to evaluate the mechanical properties or quality of concrete [ 20 , 21 , 22 ]. However, in the context of NSHC, additional research and analysis are required due to the lack of extensive experimentation.…”
Section: Introductionmentioning
confidence: 99%